Not all shrinking places are similar: The variegated nature of population decline in the United States. (January 2022) - Karp, David N.; Bagchi-Sen, Sharmistha; Rogerson, Peter
Abstract: Shrinking cities have become almost ubiquitous during the long transition of post-industrial America. While many fear population losses to be a harbinger of economic decline, others have argued that the economic and demographic transition of a shrinking city need not be a death knell for those urban communities. In this study, we conduct an analysis of more than 10, 000 U.S. census tracts experiencing population loss in order to better understand the variegated nature of population decline in the United States. Using high-dimensional cluster analysis, we classify tracts into seven distinct groups, and then assess group differences based on population characteristics and built environment indicators. Our findings show inter- and intraregional characteristics that are far from uniform. Our results imply that public policy responses cannot be developed as a one-size-fits-all strategy, nor should the outlook of urban shrinkage be understood as a nationally uniform crisis. Future work can build upon our typological definitions to offer additional insights valuable to local decision makers and leaders regarding the complex relationship between demographic change and associated socio-economic outcomes. Highlights: Heterogeneity is found among census tracts experiencing population loss. K-medoids cluster analysis detects seven distinct classes of shrinking areas. Shrinking areas are distributed across the US and show variations in socio-economic conditions. Geographic distributions of shrinking tracts reveal regional and intra-metropolitan patterns.